City as Ideology: A City Study on Divakaruni’s The Palace of Illusions - Pokhrel, Chet Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
Background: Chitra B. Divakaruni’s The Palace of Illusions (2008) revolves around the position of women in an ancient patriarchal society. The novel critiques the relationship between the various states and the political power of the ancient period, providing some insights into how a state operates properly.Methods: This paper explores the city ideology and consciousness, legends, the legacy of ancient places, and the aesthetics of ancient states. It employs the perspectives of New Historicism to interpret The Palace of Illusions, utilizing the conceptual framework of eminent scholars who shed light on general concepts of city representation in literary texts, the religious aspects of a city, and broader perspectives on the connectivity of a city.Results: The study focuses on how ancient places, palaces, and people serve as guiding principles. Written against such a backdrop and narrated by Draupadi, the daughter of King Draupada, it presents the time’s political, economic, cultural, and architectural realities. The political relations among the several states, the emergence of the states, and the aesthetics of city life are subtly reflected in the novel.Novelty: The writer depicts a city as a formidable combination of people and places, myths and legends, economy and culture, and art and architecture, which must be handled with subtlety for its existence.